Scintillation primary quenching in organic condensed media revisited - Galunov, N.Z.; Martynenko, E.V.; Semynozhenko, V.P.; Tarasenko, O.A. (Functional Materials, 2009)
The revised model of the scintillation process in organic condensed media takes into account the fundamental influence of the polarization effects on the processes proceeding in a track of ionizing particle. A very fast process of the primary quenching of the hot polaron pairs is the first "step" of "specific quenching". It defines the future processes of formation both fast and slow components of a scintillation pulse. The secondary quenching is the second "step" of "specific quenching". It takes place after track formation and thermalization. It results in decrease of the number of charge states and excited molecules. The influence of the primary quenching on "specific quenching" process is much stronger than the influence of the secondary quenching.